A revision of the Northwest Atlantic Stylasteridae (Coelenterata: Hydrozoa). - Cairns, S.D. (Smithsonian Contributions to Zoology, 1986)
The 42 species of stylasterid corals (Hydrozoa: Athecata: Stylasteridae) known from the Northwest Atlantic are described and illustrated, and their distributions are mapped. Twenty-one new species are described. The study is based on specimens collected from approximately 330 localities, including the collections of the National Museum of Natural History (USNM), Museum of Comparative Zoology (Harvard), and Rosenstiel School of Marine and Atmospheric Science, University of Miami (UMML) (USA). Previous literature on the fauna is reviewed. All species are illustrated by scanning electron micrographs, and about half of the species were examined by histological serial section of decalcified specimens. A dichotomous key to the eight western Atlanta genera and tabular keys to the species of Distichopora, Stylaster, and Crypthelia are provided. Distributional patterns of the western Atlantic stylasterids and comparisons to the distributional patterns of the ahermatypic Scleractinia are discussed. Few stylasterids have widespread distributions; 93% of the species are endemic to the western Atlantic. Stylaster roseus, the only shallow-water species, has the broadest distribution in the Caribbean. Unlike the deep-water Scleractinia, stylasterids are not present in waters directly adjacent to continental land masses, and thus do not occur in the Gulf of Mexico, off northern continental South America, or off Central America. Stylasterids are usually found in shallower water than ahermatypic Scleractinia: their depth range is rarely less than 100 m or more than 1000 m, but most commonly 150-440 m. Both groups, however, are most diverse in the Lesser Antilles and share several distributional patterns, i.e., Antillena, insular Straits of Florida, and continental slopes off the southeastern United States. Descriptors: DISTICHOPORA; STYLASTER ROSEUS; CRYPTHELIA; 21 NEW SPECIES, Crypthelia floridana, Crypthelia glossopoma, Crypthelia insolita, Crypthelia tenuiseptata, Distichopora anomala, Distichopora rosalindae, Distichopora uniserialis, Distichopora yucatanensis, Errina altispina, Lepidopora biserialis, Lepidopora clavigera, Lepidotheca brochi, Lepidotheca pourtalesi, Pliobothrus echinatus, Stenohelia pauciseptata, Stylaster aurantiacus, Stylaster corallium, Stylaster inornatus, Stylaster laevigatus, Stylaster spatula figs. 1-53, maps 1-25, appendix.